Manajemen Kurikulum Berbasis Madrasah Studi Kasus pada Madrasah Aliyah Negeri 1 Kota Metro Tahun 2017 - Subandi Subandi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Today Curriculum management is increasingly getting the attention of scientists in the field of education, it is supported by the education policy since the enactment of Law number 22 of 1999 and revised in 2004 with the new law number 32 of 2004 on regional autonomy, about decentralization so that regions have the authority to provide policy direction in education management. The purpose of the research is to describe the management of madrasah based curriculum in MAN 1 Kota Metro. Methods of data collection through interviews, observations and documents are then analyzed with descriptive qualitative. Conclusion in madrasah based curriculum management integrated with Modern boarding school (boarding school) include: 1). Planning, madrasah make curriculum based on Vision and Mission and analyze SWOT, the formulation of curriculum socialized to stakeholders then made into madrasah curriculum after obtaining validation from Ministry of Religious Province Lampung , 2) .The implementation of curriculum, madrasah in carrying out supported by a strong managerial, innovative, creative and aviation academic situation is conducive to implementing the needs of the learning environment effectively, 3). Evaluation of curriculum conducted by madrasah includes context, input, etc. Keywords: Madrasah Based Curriculum Management, Curriculum Planning & Evaluation of Madrasah Based Curriculum